Cytotoxic Triterpenoid from the Stembark of Chisocheton celebicus (Meliaceae) - Katja, Dewa Gede; Farabi, Kindi; Harneti, Desi; Mayanti, Tri; Supratman, Unang (UI Scholars Hub, 2017)
Plants belonging to the Chisocheton genus are a rich source of tetracylic triterpenoids with diverse biological activities. Two triterpenoid compounds,dammar-20,24-dien-3-one (1) and 3β-hydroxy-tirucall-7-en (2) were isolated from the stembark of Chisocheton celebicus. The chemical structures of compounds 1 and 2 were identified by spectroscopic data, including IR, NMR (1H, 13C, DEPT 135°, HMQC, HMBC, 1H-1H COSY), and MS, and they were compared with previously reported spectral data. Compounds 1 and 2 were evaluated for their cytotoxic effects against P-388 murineleukemia cells. The compounds showed cytotoxicity against P-388 murine leukemia cells, with IC50 values of 30.2 and 4.3 μg/mL, respectively.